The impact of childhood psychological maltreatment on self-referential and mother-referential processing: evidence from perception and memory - Wang, Jixian; Song, Lin; Liu, Minghui (Frontiers in Psychiatry, 2025)
BackgroundChildhood psychological maltreatment is considered one of the most severe risk factors for developing psychopathological issues in adulthood. Previous studies have preliminarily indicated that psychological maltreatment disrupts the quality of mother–child relationships, but it remains unclear whether this negative impact extends to cognitive processes.MethodsThis study examined the impact of childhood psychological maltreatment on the subjective emotional connection and objective cognitive differentiation between self and mother. The Child Psychological Maltreatment Scale was used to select 35 participants in the maltreatment group and 35 controls. The Inclusion of Other in the Self Scale was used to assess the subjective connection between self and mother. Two experiments were conducted to investigate the effects of psychological maltreatment on cognitive differentiation at the perceptual and memory levels. Experiment 1 used a self-perceptual matching task to assess the impact of maltreatment on the processing of different referential information. Experiment 2 employed the Remember/Know task to examine the influence of emotional valence and referential type on personality trait word recognition.ResultsThe CPMS negatively predicted IOS scores, indicating that psychological maltreatment reduced the subjective connection between self and mother. Perceptual and memory experimental results showed that, compared to the control group, the psychological maltreatment group did not exhibit impaired cognitive differentiation between self and mother. At the memory level, the self-referential and mother-referential effects were stronger in the maltreatment group than in the control group, but were not modulated by emotion. Emotional modulation appeared in the control group’s preference for negative emotions.ConclusionsWhile experiences of psychological maltreatment during childhood may subjectively reduce the emotional connection between self and mother, they may not impair cognitive differentiation between self- and mother-related information at the perceptual and memory levels, nor do they exhibit a negativity preference at the memory level. This study provides new evidence for understanding the mechanisms through which childhood psychological maltreatment influences self-cognitive functions in adulthood.